Multimethod U-Pb baddeleyite dating: insights from the Spread Eagle Intrusive Complex and Cape St. Mary's sills, Newfoundland, Canada - Pohlner, Johannes E.; Schmitt, Axel Karl; Chamberlain, Kevin R.; Davies, Joshua H. F. L.; Hildenbrand, Anne; Austermann, Gregor (Geochronology, 2020)
Baddeleyite (ZrO2) is widely used in U–Pb geochronology but analysis and age interpretation are often difficult, especially for samples which have experienced post-intrusive alteration and/or metamorphism. Here, we combine high spatial resolution (secondary ionization mass spectrometry, SIMS) and high-precision (isotope dilution thermal ionization mass spectrometry, ID-TIMS) analyses of baddeleyite from the Spread Eagle Intrusive Complex (SEIC) and Cape St. Mary's sills (CSMS) from Newfoundland. Literature data and our own detailed microtextural analysis suggest that at least seven different types of baddeleyite–zircon intergrowths can be distinguished in nature. These include secondary baddeleyite inclusions in altered zircon, previously unreported from low-grade rocks, and likely the first discovery of xenocrystic zircon inclusions mantled by baddeleyite. 207Pb∕206Pb baddeleyite dates from SIMS and ID-TIMS mostly overlap within uncertainties. However, some SIMS sessions of grain mounts show reverse discordance, suggesting that bias in the U ∕ Pb relative sensitivity calibration affected 206Pb∕238U dates, possibly due to crystal orientation effects, and/or alteration of baddeleyite crystals, which is indicated by unusually high common-Pb contents. ID-TIMS data for SEIC and CSMS single baddeleyite crystals reveal normal discordance as linear arrays with decreasing 206Pb∕238U dates, indicating that their discordance is dominated by recent Pb loss due to fast pathway diffusion or volume diffusion. Hence, 207Pb∕206Pb dates are more reliable than 206Pb∕238U dates even for Phanerozoic baddeleyite. Negative lower intercepts of baddeleyite discordia trends for ID-TIMS dates for SEIC and CSMS and direct correlations between ID-TIMS 207Pb∕206Pb dates and the degree of discordance may indicate preferential 206Pb loss, possibly due to 222Rn mobilization. In such cases, the most reliable crystallization ages are concordia upper intercept dates or weighted means of the least discordant 207Pb∕206Pb dates. We regard the best estimates of the intrusion ages to be 498.7±4.5 Ma (2σ; ID-TIMS upper intercept date for one SEIC dike) and 439.4±0.8 Ma (ID-TIMS weighted mean 207Pb∕206Pb date for one sill of CSMS). This first radiometric age for the SEIC is consistent with stratigraphic constraints and indicates a magmatic episode prior to opening of the Rheic Ocean. Sample SL18 of the Freetown Layered Complex (FLC), Sierra Leone, was investigated as an additional reference. For SL18, we report a revised 201.07±0.64 Ma intrusion age, based on a weighted mean 207Pb∕206Pb date of previous and new baddeleyite ID-TIMS data, agreeing well with corresponding SIMS data. Increasing discordance with decreasing crystal size in SL18 indicates that Pb loss affected baddeleyite rims more strongly than cores. Our SL18 results validate that the SIMS in situ approach, previously used for Precambrian and Paleozoic samples, is also suitable for Mesozoic baddeleyite.
Gesehen am 30.06.2021